The Effects of Work Quality and Employee Innovation on Employee Performance with Work Motivation as a Mediating Variable - Aldi Apriyanza; Desi Permata Sari; Silvia Sari (The Future of Education Journal, 2026)
This study aims to examine the effects of work quality and employee innovation on employee performance, with work motivation serving as a mediating variable, at the Public Relations and Corporate Social Responsibility (CSR) Bureau of PT Semen Padang. This study employed a quantitative research approach. Primary data were collected through questionnaires administered to 55 employees of the Public Relations and CSR Bureau of PT Semen Padang. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that work quality has a positive and significant effect on work motivation. Employee innovation also has a positive and significant effect on work motivation. Furthermore, work quality and employee innovation each have a positive and significant effect on employee performance. Work motivation likewise has a positive and significant effect on employee performance. Mediation analysis reveals that work motivation does not mediate the relationship between work quality and employee performance. However, work motivation successfully mediates the relationship between employee innovation and employee performance.